Evaluating the Acceptance and Use of Education Management Information System (EMIS) 4.0 in a Private Islamic Boarding School Based on the Technology Acceptance Model - Ara Hidayat; Elfridawati Mai Dhuhani; Hasbiyallah Hasbiyallah (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The low adoption rate of information systems in Islamic educational institutions highlights a gap between technological advancement and user acceptance, particularly within madrasa management. This study examines the acceptance and effectiveness of EMIS 4.0 in a private Islamic boarding school in Malangbong District, utilizing the Technology Acceptance Model (TAM) as the theoretical framework. A quantitative, ex post facto design was employed, with data collected from madrasa operators through questionnaires and analyzed statistically. The results indicate that management support has a significant influence on both perceived usefulness (p = 0.016) and actual system use (p = 0.022). In contrast, prior experience and training have a significant effect on perceived ease of use (p = 0.016 and p = 0.007). Although perceived usefulness does not significantly impact attitude (p = 0.416), it affects intention to use (p = 0.047), with both attitude (p = 0.029) and intention (p = 0.025) predicting actual use. This study contributes to the contextual application of TAM and offers practical strategies for sustainable EMIS adoption in faith-based schools.